2017
DOI: 10.18203/2319-2003.ijbcp20171664
|View full text |Cite
|
Sign up to set email alerts
|

A survey to assess awareness about fixed dose combinations (FDCs) among pharmacists in two Central Kashmir Districts, Srinagar and Budgam, Kashmir, India

Abstract: Background: FDCs are highly popular in Indian pharmaceutical market. The FDCs have both advantages as well as disadvantages. To be advantageous WHO guidelines for the manufacture and use of FDCs must be strictly followed. Irrational use of FDCs is a major public health problem and leads to increased risk of adverse drug events, higher treatment costs and antimicrobial resistance. FDCs as well as other single component drugs cannot be used rationally unless everyone involved directly or indirectly in the health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…[ 5 ] Yet the trend of their development and use is on the rise, especially through the previous decade, when one-third of the new drugs which were introduced in the market were FDCs. [ 6 7 ] The major concern arises when some of these combinations are irrational, as they not only increase the financial burden over both the developers and users but can also produce significant adverse effects. [ 8 ] In one of the recent analyses, it was found that out of 264 FDCs available in the market, only 54 were rational, whereas for the remaining, both the safety and effectiveness were a matter of question.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Yet the trend of their development and use is on the rise, especially through the previous decade, when one-third of the new drugs which were introduced in the market were FDCs. [ 6 7 ] The major concern arises when some of these combinations are irrational, as they not only increase the financial burden over both the developers and users but can also produce significant adverse effects. [ 8 ] In one of the recent analyses, it was found that out of 264 FDCs available in the market, only 54 were rational, whereas for the remaining, both the safety and effectiveness were a matter of question.…”
Section: Introductionmentioning
confidence: 99%